Bioaugumentation Efficiency of Microbial Bacteria and Strategy for Its Recovery through Addition of NPK Fertilizers and the Study of Its Morphology - Mohsin, Umema; Lowry, Madan; Sharma, Ranu; Moond, Mamta (International Journal of Applied Sciences and Biotechnology, 2016)
The study basically focuses on hydrocarbon contamination that is caused because of bacteria present in the soil. Transport Nagar Area in Jaipur is mostly covered with garages and hence surrounded by crude oil, petrol, diesel and other fractions of crude oil. Soil and ground water are polluted with diesel fuel from leaking underground storage tanks which happens as a result of accidental spills and leakage from pipelines which causes harm to the both flora and fauna. In the study conducted the treatment samples were observed with significant difference with the control. The microbial count was maintained in the range of 3.86*104- THBP per gram soil and 1.87*103- PDBP per gram soil. The highest bacterial growth was showed after 60 days with 40% NPK because of the presence of an inorganic nutrition, bacterial activity and as a result petroleum degradation was maximum.Int J Appl Sci Biotechnol, Vol 4(2): 233-235